Environmental Pollutants Effect on Brown Adipose Tissue - Di Gregorio, Ilaria; Busiello, Rosa Anna; Burgos Aceves, Mario Alberto; Lepretti, Marilena; Paolella, Gaetana; Lionetti, Lillà (Frontiers in Physiology, 2019)
Brown adipose tissue (BAT) with its thermogenic function due to the presence of the mitochondrial uncoupling protein 1 (UCP1), has been positively associated with improved resistance to obesity and metabolic diseases. During recent years, the potential influence of environmental pollutants on energetic homoeostasis and obesity development has drawn increased attention. The purpose of this review is to discuss how regulation of BAT function could be involved in the environmental pollutant effect on body energy metabolism. We mainly focused in reviewing studies on animal models, which provide a better insight into the cellular mechanisms involved in this effect on body energy metabolism. The current literature supports the hypothesis that some environmental pollutants, acting as endocrine disruptors (EDCs), such as dichlorodiphenyltrichoroethane (DDT) and its metabolite dichlorodiphenylethylene (DDE) as well as some, traffic pollutants, are associated with increased obesity risk, whereas some other chemicals, such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), had a reverse association with obesity. Noteworthy, the EDCs associated with obesity and metabolic disorders impaired BAT mass and function. Perinatal exposure to DDT impaired BAT thermogenesis and substrate utilization, increasing susceptibility to metabolic syndrome. Ambient particulate air pollutions induced insulin resistance associated with BAT mitochondrial dysfunction. On the other hand, the environmental pollutants (PFOS/PFOA) elicited a reduction in body weight and adipose mass associated with upregulation of UCP1 and increased oxidative capacity in brown-fat mitochondria. Further research is needed to better understand the physiological role of BAT in response to exposure to both obesogenic and anti-obesogenic pollutants and to confirm the same role in humans.